Analisis Kualitas Keripik Tempe Di UD. Bu Las Desa Maluk Menggunakan Metode Voice Of Customer (VOC) - Ismi Mashabai; Rusmalah Rusmalah; Ruspendi Ruspendi (Fakultas Teknik Universitas Tulang Bawang, 2023)
Quality is very important in choosing products besides competitive prices. UD. Bu Las is a Small and Medium Enterprise (UKM) located in Maluk Loka, Kab. West Sumbawa was founded in 1997 by Mrs. Welas Asih with the main product being tempeh chips. The many similarities in products produced by SMEs give rise to competition in the sale of tempeh chips. The aim of the quality analysis research is to ensure that the tempe chips products produced can compete with other SMEs. Voice of Customer is a process used to capture needs or feedback from customers as a means of providing service/product quality. Apart from that, of course you will get the information you are looking for regarding customer expectations and needs as input that the company must consider when making decisions. Results from Voice of Customer of Ud Bu Las customers with 25 statements to 10 consumers, namely, balado taste score 45%, round shape score 49%, price Rp. 2,500 20g size scores 48%, expiry date scores 45% and slice thickness scores 45%. Suggestions for improvement are (1) for the taste, not just 1 variant, (2) the shape of the chips is not monotonous, (3) the price is the same as the more economical size variant, (4) the packaging is vacuum packed so that the expiry period is longer, (5) the dimensions of the tempeh so there are many variants. Keywords: Quality of tempe chips, Voice of Customer, UD. Bu Las